2004
DOI: 10.1111/j.0953-816x.2004.03425.x
|View full text |Cite
|
Sign up to set email alerts
|

Organization of prefrontal outflow toward frontal motor‐related areas in macaque monkeys

Abstract: Linkage between the prefrontal cortex and the primary motor cortex is mediated by nonprimary motor-related areas of the frontal lobe. In an attempt to analyse the organization of the prefrontal outflow from area 46 toward the frontal motor-related areas, we investigated the pattern of projections involving the higher-order motor-related areas, such as the presupplementary motor area (pre-SMA) and the rostral cingulate motor area (CMAr). Tracer injections were made into these motor-related areas (their forelimb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
51
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 59 publications
9
51
0
Order By: Relevance
“…In contrast, dorsal area 46 exhibited much weaker labeling. This indicates that ventral area 46, but not dorsal area 46, is preferentially involved in the control of forelimb movements, albeit both areas are directly interconnected with the rostral motor-related areas (Arikuni et al, 1980;Barbas and Pandya, 1987;Lu et al, 1994;Takada et al, 2004). Consistent with our findings, previous physiological studies have reported that ventral area 46 neurons were specifically activated during the performance of delayed response tasks, in which monkeys responded manually (di Pellegrino and Wise, 1991;Hoshi et al, 1998;Rainer et al, 1998).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In contrast, dorsal area 46 exhibited much weaker labeling. This indicates that ventral area 46, but not dorsal area 46, is preferentially involved in the control of forelimb movements, albeit both areas are directly interconnected with the rostral motor-related areas (Arikuni et al, 1980;Barbas and Pandya, 1987;Lu et al, 1994;Takada et al, 2004). Consistent with our findings, previous physiological studies have reported that ventral area 46 neurons were specifically activated during the performance of delayed response tasks, in which monkeys responded manually (di Pellegrino and Wise, 1991;Hoshi et al, 1998;Rainer et al, 1998).…”
Section: Discussionsupporting
confidence: 91%
“…Likewise, many of the labeled neurons in the prefrontal cortex can be considered third-order neurons, because conspicuous labeling of striatal neurons and Purkinje cells appeared coincidently. Our quantitative analysis has revealed that the number of labeled neurons was increased exponentially, first in the caudal motor-related areas, then in the rostral motor-related areas, and finally in the prefrontal areas (Bates and Goldman-Rakic, 1993;Luppino et al, 2003;Takada et al, 2004). In addition, the rapid increase in labeled neuron number could be ascribed to transneuronal labeling through intrinsic and/or bypath circuits.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…It has been argued that the caudal CMA can be subdivided into dorsal and ventral (CAMv) components. In the monkey, all of the cingulate motor areas are interconnected with dorsal and ventral divisions of lateral premotor cortex (Barbas and Pandya, 1987;Luppino et al, 1998Luppino et al, , 2003Hatanaka et al, 2003;Takada et al, 2004). There is little evidence for connections between the cingulate gyrus, ventral and posterior to the CMAs, and the lateral premotor cortex.…”
Section: Definition Of Target Masksmentioning
confidence: 99%
“…cortical plasticity | frontal executive function T he primate dorsomedial prefrontal cortex (PFC), and particularly its posterior region (pmPFC), is intimately connected with higher-order cortical motor areas in the frontal lobe, including the presupplementary motor area (pre-SMA), the rostral cingulate motor area, and the dorsal premotor area (1)(2)(3)(4). This relationship with cortical motor areas resembles connections from the dorsolateral PFC (dlPFC), suggesting that both areas influence downstream motor areas during the selection, preparation, and execution of actions (5)(6)(7)(8).…”
mentioning
confidence: 99%